Empirical validation of the information-motivation-behavioral skills model of gestational weight management behavior: a framework for intervention - Hua You; Yuan-Yuan Wang; Chi Zhang; Anita Nyarkoa Walker; Jin-Jin Ge; Shi-Qi Zhao; Xue-Qing Peng (BMC, 2023)
Abstract Background Unhealthy gestational weight gain is a modifiable risk factor for adverse maternal and child health. Appropriate and effective intervention strategies that focus on behavioral change or maintenance are critical in weight management during pregnancy. Our aim was to uncover the influencing factors and psychosocial mechanisms of gestational weight control behavior, and to construct a behavioral model suitable for intervention based on Information-Motivation-Behavioral skills (IMB) model. Methods A sample of 559 pregnant women from a municipal maternal and child healthcare facility in Jiangsu Province, China was enrolled in this cross-sectional empirical study. Partial least square structural equation modelling was used to verify the hypothesized model, and post hoc analyses was used to test the effect of parity and pre-pregnancy BMI on the model. Results The IMB model elements can predict gestational weight management (GWM) behavior well, with information being the most influential factor. As predicted, information affects GWM directly (β = 0.325, p < 0.05) and indirectly (β = 0.054, p < 0.05) through behavioral skills. Likewise, motivation has direct (β = 0.461, p < 0.05) effects on GWM, and has indirect (β = 0.071, p < 0.05) effects through behavioral skills. Behavioral skills have a direct impact (β = 0.154, p < 0.05). The model had a goodness of fit (GOF = 0.421) and was robust when tested in subgroups of different parity or pre-pregnancy BMI. Conclusion Findings from this study supported the predictions of the IMB model for GWM behavior, and identified its modifiable determinants. The tested behavior model for GWM can serve as a new validated intervention strategy in weight management among pregnant women.